Hubungan Penyesuaian Diri dan Pola Asuh Demokratis dengan Motivasi Belajar Siswa Kelas 7 Sekolah Menengah Pertama - Camelia rizkia Harahap; Saiful Akhyar Lubis; Nina Siti Salmaniah Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the relationship between Adaptation and Democratic Parenting Patterns with Learning Motivation of Grade 7 students of SMP Shafiyyatul Amaliyyah Medan, with a population of 114 students. The research sample was 45 students. The method used in this research is quantitative method with sampling technique using purposive sampling technique. The instrument used is a Likert scale model questionnaire. The data collection technique used three scales consisting of the self-adjustment, democratic parenting and learning motivation scales. The analysis technique used is Multiple Regression. Based on the results of the study, it was concluded that: 1) Self-adjustment was positively related to student learning motivation as indicated by a correlation coefficient of R = 0.369. Where the contribution of the X1 variable to the Y variable is R2 = 13.6%. 2) Democratic parenting has a positive relationship with student learning motivation as indicated by a correlation coefficient of R = 0.302. Where the contribution of the X2 variable to Y is R2 = 9.1%. 3) Adaptation and Democratic Parenting together have a relationship with learning motivation of R = 0.434. Where the contribution of variables X1 and X2 to Y is R2 = 18.9%. From these results it can be said that the higher the self-adjustment and democratic parenting, the higher the learning motivation, and conversely the lower the self-adjustment and democratic parenting, the lower the motivation. student learning.